Jak nas czytają za granicą? Ankieta - Zhenhui, Zhang (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
In response to the questions posed in the questionnaire, the scholar discusses the interest in Polish culture in China, considering the status of Polish literature in Europe and pointing to its characteristic feature — patriotism. When asked about the most important works, both for him and the readers from his cultural circles, he lists: Pan Tadeusz, Quo Vadis, The Doll and The Literary Work of Art by Roman Ingarden.